- -

Solved Examples
Click on a 'View Solution' below for other questions:
 D   If 2x2 - 2xy = 4, then find dxdy using implicit differentiation.   D View Solution
 D   If 6c3 - 5y3 = 8cy, then find dydc by using implicit differentiation.   D View Solution
 D   If 6e(7x2+8y2) = 7y, then find dydx using implicit differentiation.   D View Solution
 D   If 25z2 + 9zy + 11y2 = 0, then find dzdy using implicit differentiation.   D View Solution
 D   If 9y cos (4y + 22) = c, then find dydc using implicit differentiation.   D View Solution
 D   If 2a3 + 2y3 = 3y, then find dyda.   D View Solution
 D   If y = sin- 1 x on (- 1, 1), then find dydx using implicit differentiation.   D View Solution
 D   If y = cos- 1 x on (- 1, 1), then find dydx using implicit differentiation.   D View Solution
 D   Find the derivative of tan- 1 x on R.   D View Solution
 D   Find the derivative of sec- 1 x on R - [- 1, 1].  ff View Solution
 ff  If y = sinh- 1 x, then find dydx on R using implicit differentiation.  ff View Solution
 ff  Find the derivative of cosh- 1 x on (1, ∞).  ff View Solution
 ff  Find the derivative of tanh-1 x on (- 1, 1).  ff View Solution
 ff  Find the derivative of csch-1 x on R - {0}.  ff View Solution
 ff  If e4sin (a + 42) + 3ay = 5, then find dady using implicit differentiation.  ff View Solution
 ff  If (x + y)2 = 4y - 5x - 7, then find the value of dydx using implicit differentiation.  ff View Solution
 ff  If cy = cos (7c + 4y), then find dydc using implicit differentiation.  ff View Solution
 ff  If y = 5x3y2 + 4xy3, then find dydx using implicit differentiation.  ff View Solution
 ff  If 5cos2x + 3cot2y = 5x, then find dydx using implicit differentiation.  ff View Solution
 ff  If cy = 7c2+2y2, then find dcdy using implicit differentiation.  ff View Solution
 ff  If y = ex, then find dydx using implicit differentiation.  ff View Solution
 ff  If y = ln x, then find dydx using implicit differentiation.  ff View Solution
 ff  If 6sin (x - y) - 4cos (x + y) = 138, then find dydx using implicit differentiation.  ff View Solution
 ff  If 2(u - v)2 + 5uv = 41, then find dvdu using implicit differentiation.  ff View Solution
 ff  If 5a2 + 2y2 = 41(sin a), then find y′ using implicit differentiation.  ff View Solution
 ff  If 2c² + cy + 3y² = 23, then find y′ using implicit differentiation.  ff View Solution
 ff  If 2x - 9y = 10xy, then find dydx by using implicit differentiation.  ff View Solution
 ff  If y = (6z + 3)(7z + 4y), then find dydz using implicit differentiation.  ff View Solution
 ff  If 7zy = 3sin (zy + 44), then find y′ using implicit differentiation.  ff View Solution
 ff  If 4b14 - 3y13 = 43, then find y′ using implicit differentiation.  ff View Solution
 ff  If 7z + 4y7z - 4y = 4zy, then find y′ using implicit differentiation.  ff View Solution
 ff  If y + 2y4 + 3b2 = 39, then find y′ using implicit differentiation.  ff View Solution
 ff  If 5c7 = 6y3cos y, then find y′ using implicit differentiation.  ff View Solution
 ff  If 3z5 + y5z = 24, then find y′ using implicit differentiation.  ff View Solution
 ff  If y + 2tan2x = 3cot2y, then find y′ using implicit differentiation.  ff View Solution